Pengaruh Kepemimpinan Digital terhadap Kelincahan Organisasi melalui Kompetensi Karyawan pada UMKM di Purwakarta - Nurniawan, Heppy; Amalia, Dinda (Awatara Publisher, 2025)
This study investigates the role of digital leadership in enhancing organizational agility through employee competence in Micro, Small, and Medium Enterprises (MSMEs) in Purwakarta, Indonesia. Drawing on the Dynamic Capability Theory, the research employs a qualitative approach with eight key informants from various MSMEs. Findings reveal that digital leadership is pivotal in promoting a culture of learning, autonomy, and innovation, thereby fostering employee competence. Competence, in turn, mediates the relationship between leadership and agility by enabling employees to respond quickly and effectively to market and operational shifts. The study identifies both formal and informal mechanisms of competence development, emphasizing the importance of leadership-driven learning in resource-constrained environments. Moreover, the results highlight how decentralized structures and open communication contribute to agility by enhancing coordination and responsiveness. The findings contribute to a multilevel understanding of how individual behaviors, team dynamics, and strategic leadership coalesce to build organizational agility. Practical implications include the need for targeted leadership development and alignment of HR practices with digital transformation strategies. Limitations include a small sample size and the absence of sectoral comparisons, which future studies should address through broader and more diversified designs. Ultimately, the study underscores the importance of leadership and human capital as interconnected enablers of agility in MSMEs navigating digital disruption.